Navigating the double-edged sword: How and when laissez-faire leadership affects Employees' challenging behavior - Shanting Zheng; Lingli Li (Acta Psychologica)
The majority of extant studies have found the detrimental role of laissez-faire leadership, but some researchers have revealed its potential benefits. The current research aims to investigate the double-edged nature of laissez-faire leadership. Drawing upon conservation of resources theory, we identify both the dark and bright sides of laissez-faire leadership because the nature of laissez-faire leaders not providing support resources can be perceived by employees as offering limited guidance from the resource loss perspective and offering freedom resources from the resource gain perspective. We propose and test the effects of laissez-faire leadership on employees' constructive challenging behavior through the mediators of work-related flow and work disengagement, and we posit that this mediating relationship is conditional on the moderator of coworker-support climate. Three independent studies (i.e., two vignette experiments in Study 1 with 52 participants and Study 2 with 77 participants, and a time-lagged field study in Study 3 with 277 employees) were conducted to consistently indicate the double-edged nature of laissez-faire leadership. Specifically, on the one hand, laissez-faire leadership is positively associated with subordinates' increased work disengagement, which in turn reduces their constructive challenging behavior (Study 1 and Study 3). On the other hand, laissez-faire leadership is positively associated with subordinates' work-related flow, which in turn enhances their constructive challenging behavior (Study 2 and Study 3). In addition, the coworker-support climate was found to positively moderate the relationship between laissez-faire leadership and subordinates' constructive challenging behavior via work-related flow.